2015
DOI: 10.1044/2015_jslhr-s-14-0277
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Masking Effects on Speech Fluency in Apraxia of Speech and Aphasia: Comparison to Altered Auditory Feedback

Abstract: Speaking with MAF appears to increase fluency in a subset of individuals with APH/AOS, indicating that overreliance on auditory feedback monitoring may contribute to their disorder presentation. The distinction between responders and nonresponders was not linked to AOS diagnosis, so additional work is needed to develop hypotheses for candidacy and underlying control mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 76 publications
1
16
0
Order By: Relevance
“…Similar to the internal attention account, overreliance on auditory feedback might disrupt automatization by causing speakers with AOS to focus internally on acoustic or movement patterns of their speech (Jacks, 2008;Maas et al, 2008). Restricting access to auditory feedback with continuous masking noise might decrease disfluencies in AOS by causing speakers to attend less to their errors (Jacks & Haley, 2015). Similarly, distracting people from conscious control of their speech through a dual task might also redirect attentional resources from internal focus on feedback.…”
Section: Effects Of Cognitive Demandsmentioning
confidence: 99%
“…Similar to the internal attention account, overreliance on auditory feedback might disrupt automatization by causing speakers with AOS to focus internally on acoustic or movement patterns of their speech (Jacks, 2008;Maas et al, 2008). Restricting access to auditory feedback with continuous masking noise might decrease disfluencies in AOS by causing speakers to attend less to their errors (Jacks & Haley, 2015). Similarly, distracting people from conscious control of their speech through a dual task might also redirect attentional resources from internal focus on feedback.…”
Section: Effects Of Cognitive Demandsmentioning
confidence: 99%
“…We further predicted that PPA syndromes would show differential sensitivity to DAF, and that individual variation within groups would lead to departures from any group-wise profiles. At group level, extrapolating from previous observations in stroke aphasia ( 14 , 22 , 24 ), we hypothesized an overall increased sensitivity to DAF in nfvPPA, less marked sensitivity in svPPA and a mixed profile in lvPPA. We anticipated that group profiles of altered DAF sensitivity in the ‘non-aphasic' syndromes of bvFTD and tAD would be comparable to healthy older individuals.…”
Section: Introductionmentioning
confidence: 72%
“…The speech slowing and speech sound errors induced by DAF in healthy individuals closely resemble the speech production deficits that characterize nfvPPA ( 5 ), hinting at a shared cognitive or pathophysiological mechanism and the possibility of therapeutic applications. Evidence in stroke populations has suggested that sensitivity to DAF may vary between aphasic syndromes, with less sensitivity in fluent and conduction aphasia albeit with considerable variability between reports ( 14 , 22 – 24 ): this potentially opens up a novel avenue to syndrome stratification and diagnosis in the PPA spectrum, which continues to pose substantial nosological difficulties ( 20 ). Neuroanatomically, the effects of DAF and other forms of altered auditory feedback (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Because AOS is commonly co-morbid with aphasia, as in this current study, certain researchers (e.g. Bailey et al, 2017;Jacks and Haley. 2015) have discussed the possibility of an overlap of certain disfluencies, such as revisions, that may originate from both motor and linguistic deviations.…”
Section: Deviant Fluency Following Tbimentioning
confidence: 94%